Evaluation of Brønsted acidity and proton topology in Zr- and Hf-based metal-organic frameworks using potentiometric acid-base titration - Klet, Rachel C; Liu, Yangyang; Wang, Timothy C; Hupp, Joseph T; Farha, Omar K (Journal of materials chemistry. A, Materials for energy and sustainability, 2016)
Potentiometric acid-base titration is introduced as a method to evaluate p K a values (Brønsted acidity) of protons present in the nodes of water stable Zr 6 - and Hf 6 -based metal-organic frameworks (MOFs), including UiO-type MOFs, NU-1000, and MOF-808. p K a values were determined for the three typical types of protons present in these MOFs: μ 3 -OH, M-OH 2 , and M-OH (M = Zr, Hf). Additionally, the data was used to quantify defect sites resulting from either a surfeit or shortage of linkers in the MOFs and to provide information about the true proton topology of each material. Potentiometric acid-base titration is introduced as a method to evaluate p K a values (Brønsted acidity) of protons present in the nodes of water stable Zr 6 - and Hf 6 -based metal-organic frameworks (MOFs), including UiO-type MOFs, NU-1000, and MOF-808.